Geophysical prospection for mapping of the qanat systems: apllication to the qanat system of Agia Paraskevi - Choartiati of Thessaloniki (Ν. Greece) - TSOURLOS, P.; VARGEMEZIS, G.; TSOKAS, G.; ALEXANDROU, K.; TZELI, P. (Bulletin of the Geological Society of Greece, 2001)
In this paper the application of the 2-D electrical and ground penetrating radar (GPR) geophysical techniques for locating subsurface water collective systems (qanats) is demonstrated. Qanats can be found in many Greek regions and despite the fact that most of them are inactive, in some areas qanats are still being used as water providing systems. For both environmental and historical reasons there is a need that existing qanats are protected, fully mapped and studied in view of their geological and hydrogeological environment. Geophysics can play a significant role in this procedure. Synthetic modeling and inversion examples presented in this work support the above claim. Further, in this paper the electrical and GPR techniques are used to map a well-known and already studied Qanat system at the area of Agia Paraskevi at the outskirts of the Chortiatis village 20 kilometers away from the city of Thessaloniki. The interpreted features delineated by the geophysical techniques are in very good agreement with the known qanat structure. Overall, it is shown that geophysical techniques can be used to aid qanat mapping as well as to provide useful information about their general setting.